Symbolika eklezjalna Jerozolimy a polemika antydonatystyczna w Afryce Rzymskiej - Paczkowski, Mieczysław Celestyn (Vox Patrum, 2019)
The presented article analyses to which extent the African authors had got used of the image of Jerusalem in the period of their polemic with the Donatists. It is well known that one of the focal points of the Donatist controversy concerned ecclesiology. There is a great number of Church’s images occurring in the works of Christian authors, but it seems that a symbol of Jerusalem is however predominant. The city of God, an image of the Church, revealed itself as an earthly and celestial reality, including both the historical sphere and transcendence. Already in the process of forming ecclesiology in Nord Africa had a particular physiognomy with elements assimilated and altered by the Donatist sect. The reflections of Tyconius and Optatus of Milevi took on considerable significance and stood at the origin of catholic’s inspiration and argumentation. St. Augustine of Hippo placed the conflict with the Donatists not only on the practical and disciplinary context but above all on the doctrinal level. His ecclesiology proved to be coherent and compact. The bishop of Hippo found his basis on the biblical level and the traditional doctrine. In the anti-Donatist literature, it can be observed a certain predilection for a particular set of scriptural quotations used by various authors as an argument and as an illustration to support the thought concerning the universality of the Church. The topic of Jerusalem played here the crucial role.